Mastering English Multiple Adjectives Ordering among Early versus Late Second Language Speakers: Evidence from Arabic-English Bilinguals - Albaqami, Rashidah (International Journal of Language and Literary Studies, 2023)
Recent research has shown that learners demonstrate huge variability in second language (L2) end-state attainment. While some L2 learners attain native-like command, others only attain an undeveloped command and some stuck in between. It is also assumed that early learners often surpass owing to Lenneberg’s Critical Period Hypothesis (1967) that proposes that early onset often advance L2 development. This study investigates the extent to which, age is associated with mastering the target language among late versus early Arabic-English bilinguals. Specifically, this study concerns itself with the issue of how Arabic-English bilinguals typically perceive the right ordering of multiple consecutive adjectives (e.g., the small yellow bird). A considerable amount of literature has established that L2 learners encounter challenges in mastering the right sequence of adjectives, particularly when there are several adjectives modifying a single noun. To determine how Arabic-learners of English perceive English descriptive adjective orderings, this study observes whether an earlier age of first contact with English enhances the learners’ accuracy and the reaction time. To test this assumption, the intuitions of two groups of early (n=8) vs. late (n=8) Arabic-English bilinguals in the United Kingdom (i.e. Leeds) were compared for English descriptive adjective ordering preferences through a Speeded Acceptability Judgment Task (SAJT). The participants were requested to show their ordering preferences for a couple of multi-adjective strings (n=16). The findings suggested that early Arabic-English bilinguals significantly outperformed late Arabic-English bilinguals in terms of exhibiting native-like ordering preferences. The study concludes that early exposure is more likely to facilitate mastering the target system and that it generally accelerates L2 development. This study also concludes that accuracy and response time may reflect the L2 development. The study suggests a number of pedogeological implications for teaching and learning an L2.